THE CONSTITUTIONALISATION OF THE FUNDAMENTAL CIVIL RIGHTS AND CHALLENGES OF ITS EFFECTIVENESS: CONSIDERATIONS ON THE MORAL INTERPRETATION OF THE CONSTITUTION - Castro, Matheus Felipe; Freitas, Riva Sobrado de (Unoesc International Legal Seminar, 2017)
We seek to develop in this work a critical approach about the Constitutionalisation phenomenon of Fundamental Rights nowadays, seeking to understand the challenges surrounding this issue, especially with regard to changes and disruptions promoted by irradiation of constitutional values to the whole legal system. Proposal innovative and with great powers of seduction, especially the possibility of realizing substantial justice and significant progress for social inclusion, we have seen emerge and radiate the expansive effect that the constitutional requirements have acquired, especially in the last 50 years in the face of Constitutionalisation of Fundamental Rights. The force from the Constitution focused mainly on the material and axiological content of constitutional norms, which have to condition the validity and meaning of all the infra-constitutional norms, projecting into the legal system, and in this perspective, moving away than traditionally was known until now as Supremacy of the Constitution, as Kelsen model. On the other hand, we observed that Constitutionalisation of Fundamental Rights significantly approached the contemporary Philosophy, building through constitutional hermeneutics a proposal for rapprochement between law and morals, making mandatory the embodiment of moral content arranged on Fundamental Rights. Thus, we saw the affirmation of a new constitutional interpretation, taking as its starting point the specificity of the Constitution, to present constitutional values with legal force and legal effect. Depending on this new approach, there would be a counterpoint between the "real constitution" (written text of constitutional norms) and the "ideal constitution," playing the first by irradiation values derived from the second. The legitimating justification for that would be the search for substantial justice to move towards a more appropriate decision, able to promote the necessary social inclusion. However, if it is real the possibility of progress on the path of material justice, and social inclusion, some considerations must be made regarding the impact of anti-positivist thesis in the Constitutionalisation of Fundamental Rights, including: the issue of legal certainty; the formulation of any particularistic and authoritarian decisions; apart from the difficulty of building a moral thesis by the judiciary, able to contemplate the diversity of Justice concepts in an extremely fragmented contemporary society. These considerations, and others discussed in this text, were the object of our investigations in this work, always with a view to achieve the limit of these theoretical formulations and the risks of a judicial activity extremely subjective and with wide discretion. Our goal in this opportunity was so only promote the necessary reflections from a theoretical point of view, without performing case studies, which will certainly be focused later.